Nematic liquid crystal 4-cyano-4′-pentylbiphenyl functionalization of MWNTs for improved thermal and mechanical properties of silicone pressure sensitive adhesives. (April 2020) - Zheng, Jinbao; Zong, Yangyang; Zhao, Gaiqing; Yu, Zhenqiang; Wang, Mingliang; Zhu, Caizhen; Li, Cuihua; Liu, Jianhong; Gui, Dayong
Abstract: In this research, nanocomposite modified pressure sensitive adhesives (PSA) (5CB-MWNTs/PSA) with high mechanical and thermal properties were fabricated via nematic liquid crystal 4-cyano-4′-pentylbiphenyl (5CB) functionalized multi-walled carbon nanotubes (MWNTs). The results showed that 5CB interacted with MWNTs via non-covalent interactions e.g. π-π stacking, which not only improved the dispersion and orientation of MWNTs in a silicone PSA but also the compatibility between MWNTs and the silicone material. The tensile strength of 5CB-MWNT/PSA was increased to 14.5 MPa while the mass fraction of MWNTs was 1.0%, which was an enhancement of 943% over that of the MWNTs/PSA and 28 times greater than that of the neat PSA. In addition the thermal conductivity of the PSAs filled with the 5CB-MWNTs were improved to 1.28 W/(mK) at a mass fraction of 10%, which was increased by 552% over that of the neat PSA and 231% over that of the MWNT/PSA. The resulting thermally conductive and mechanically applicable silicone PSA nanocomposites could be significant in a wide variety of pressure sensitive adhesive applications.